The formation of the ego in the Mirror Stage: the construction of identity in Lacanian psychoanalysis (Interapia – Journal of Clinic, Culture and Mental Sciences, 2025)
AbstractThe article examines the process of ego formation according to Lacan’s Mirror Stage theory, showing how imaginary identification grounds the subject’s identity and alienation. It highlights the clinical and theoretical importance of understanding the ego as a symbolic and fictional construct.
Keywords: Lacan; ego; identity; Mirror Stage; psychoanalysis